Chlorogenic acid loaded niosomes and proniosomes: in vitro antioxidant and antibacterial activities with efficacy in wound healing - Hemangi Ramesh Trivedi; Prashant Keshao Puranik (KeAi Communications Co., Ltd., 2023)
Objective: To develop and optimize niosomal and proniosomal vesicular delivery systems for a naturally occurring polyphenol chlorogenic acid (CGA), so as to improve its physicochemical properties and permeability, which may enhance its pharmacological activity. Methods: The formulated CGA niosomes (CGANs) and CGA proniosomes (CGAPNs) were primed by thin film hydration and phase separation coacervation methods, and were characterized with different attributes including particle size, morphology, entrapment efficiency, zeta potential, deformability, in vitro diffusion, ex vivo permeability, and long-term stability. Their efficiency was further evaluated with in vitro antioxidant assay, antibacterial assays, and excision wound healing model in rats. Results: Optimized CGANs and CGAPNs showed spherical vesicles with particle size of 490.1 ± 43.0 and 280.0 ± 22.0 nm, polydispersity index (PDI) values of 0.526 and 0.173, and stable zeta potential values of - 29.3 ± 6.4 and - 33.2 ± 6.5 mV, respectively. The CGANs and CGAPNs vesicles showed higher entrapment (98.27% ± 0.46% & 97.27% ± 0.25%) with good deformability (8.77 ± 0.22 & 6.87 ± 0.17), higher in vitro diffusion (97.96% ± 1.67% & 91.00% ± 1.32%), and permeability coefficient values (67 × 10-3 ± 1.72 & 52 × 10-3 ± 1.09) with long-term stability in comparison with plain CGA. Enhanced 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and Fe2 + chelation ability was obtained with CGAPNs > CGANs. They also demonstrated lethal bactericidal activity on different gram positive and gram negative strains with lower minimum inhibitory concentration (MIC) values (8 × and 16 × times less) as compared with plain CGA. Significant reduction (P < 0.05) in wound area with higher wound contraction percentages on day 9 was observed with CGANPs (99.56%) > CGANs (98.44%) in comparison with marketed (92.89%) and CGA (88.89%) hydrogel. Conclusion: These results show great potential of CGANs and CGAPNs for topical wound healing application. This is the first study of CGA in niosomal and proniosomal topical delivery systems.